Morphometric and Ki-67 proliferative index-related characteristics of meningiomas and their correlation with demographic, clinical, histopathological, and postoperative features - Ragib Pugonja; Hakija Bečulić; Emir Begagić; Rasim Skomorac; Edin Selimović; Mirza Moranjkić (Medicinski glasnik, 2023)
Aim: To investigate the correlations between tumour characteristics, symptoms, intraoperative findings, and outcomes in patient with meningioma. Methods: A retrospective study was conducted on 86 surgically treated patients at Department of Neurosurgery of Cantonal Hospital Zenica from 2010 to 2020. Patients with intracranial meningiomas underwent neurological evaluation and MRI scans to analyse tumour characteristics, including volume (TV), peritumoral brain oedema (PTBE) and oedema index (EI). Surgical treatment was performed, followed by postoperative MRI and outcome assessment. Intraoperatively, the tumour’s relationship with cortex, pial membrane, skull bones, and sinuses was evaluated, and the extent of tumour resection was graded. Meningioma samples underwent histopathological analysis to assess the grade and regularity of borders, and Ki-67 labelling index was determined using immunohistochemistry. Results: Significant correlations were found between PTBE and Ki67 expression (p<0.001), PTBE and vomiting/nausea (p=0.002), cognitive impairment (p=0.047), venous compression (p=0.001), cortical, pial and dural invasion (p<0.05), and the postoperative presence of oedema (p=0.002). Venous compression, cortical, pial, dural and bone invasion positively correlated with Ki-67 expression (p<0.001). Grade and tumour border positively correlated with Ki-67 expression (p<0.001). Oedema persistence postoperatively showed a positive correlation with Ki-67 expression (p<0.001). Conclusion: The study revealed significant correlations between Ki-67 expression and PTBE, with notable associations with clinical symptoms, tumour characteristics, and postoperative oedema presence.
Keywords: brain oedema; brain neoplasms; morphometry; tumour volume; volumetry